Pertunjukan Wayang Babad Nusantara: Wahana Pengajaran Nilai Kebangsaan bagi Generasi Muda - Sunardi -; Sugeng Nugroho; Kuwato - (LP2M ISBI Bandung, 2016)
ABSTRACT Wayang Babad Nusantara represents a creation of a shadow puppet show which used as a means of transmission of nationalism values towards younger generations. This type of show has the aspect of innovations in several elements of pakeliran, which are: the heroic story of National heroes’ struggle, the authentic puppets bas on the reinterpretation of the figure in the history, a new musical score, and the scene-system with the shadow puppet show structure. This show is interestingly wrapped with the story of Gajah Mada. The spirit of these figure serves as the good example for young generations to love their country. The nationalism value, which contain the teaching of patriotism and allegiance can build the awareness of the children of the nation so that they will always love the land of Indonesia. Keywords: Babad shadow puppet, nationalism values, young generations ABSTRAK Wayang Babad Nusantara merupakan rekayasa model pertunjukan wayang yang dipergunakan sebagai wahana transmisi nilai-nilai kebangsaan bagi generasi muda. Pertunjukan wayang ini memiliki kebaruan dalam berbagai unsur pakeliran, yaitu: cerita sejarah perjuangan pahlawan bangsa, boneka wayang hasil reinterpretasi dari figur tokoh, musik komposisi baru, dan sistem pengadegan dengan struktur pertunjukan wayang. Pertunjukan wayang ini dikemas secara menarik dengan menyajikan cerita Gajah Mada. Spirit perjuangan tokoh Gajah Mada ini memberikan suri teladan bagi generasi muda untuk selalu cinta tanah air. Nilai kebangsaan yang memuat ajaran mengenai patriotisme dan nasionalisme memberikan kesadaran dan menggugah kesadaran anak bangsa untuk selalu mencintai Tanah Air Indonesia. Kata kunci: wayang babad, nilai kebangsaan, generasi muda